The Induction of an Effective dsRNA-Mediated Resistance Against Tomato Spotted Wilt Virus by Exogenous Application of Double-Stranded RNA Largely Depends on the Selection of the Viral RNA Target Region - Tabein, Saeid; Jansen, Marco; Noris, Emanuela; Vaira, Anna Maria; Marian, Daniele; Behjatnia, S. Ali Akbar; Accotto, Gian Paolo; Miozzi, Laura (Frontiers in Plant Science, 2020)
Tomato spotted wilt virus (TSWV) is a devastating plant pathogen, causing huge crop losses worldwide. Unfortunately, due to its wide host range and emergence of resistance breaking strains, its management is challenging. Up to now, resistance to TSWV infection based on RNA interference (RNAi) has been achieved only in transgenic plants expressing parts of the viral genome or artificial microRNAs targeting it. Exogenous application of double-stranded RNAs (dsRNAs) for inducing virus resistance in plants, namely RNAi-based vaccination, represents an attractive and promising alternative, already shown to be effective against different positive-sense RNA viruses and viroids. In the present study, the protection efficacy of exogenous application of dsRNAs targeting the nucleocapsid (N) or the movement protein (NSm) coding genes of the negative-sense RNA virus TSWV was evaluated in Nicotiana benthamiana as model plant and in tomato as economically important crop. Most of the plants treated with N-targeting dsRNAs, but not with NSm-targeting dsRNAs, remained asymptomatic until 40 (N. benthamiana) and 63 (tomato) dpi, while the remaining ones showed a significant delay in systemic symptoms appearance. The different efficacy of N- and NSm-targeting dsRNAs in protecting plants is discussed in the light of their processing, mobility and biological role. These results indicate that the RNAi-based vaccination is effective also against negative-sense RNA viruses but emphasize that the choice of the target viral sequence in designing RNAi-based vaccines is crucial for its success.